Effects of silica nanoparticles on glass and carbon fiber epoxy composites (Nexo Revista Científica, 2023)
In a variety of industries, including construction, automotive, marine, and aerospace, hybrid composite materials have great promise as engineering materials. By carefully choosing both the fibers and matrix employed, they enable designers to obtain desired qualities to a significant degree. The qualities of the material may be altered and adapted by adding various fiber types to a common resin matrix. In order to assess their potential for structural applications, the mechanical properties of a glass and carbon fiber epoxy composite reinforced with silica nanoparticles were examined and compared to those of clean epoxy. The samples were created using the vacuum bag process and heat-cured regardless of the laminated material. To guarantee accurate and trustworthy findings, mechanical characteristics including E1, E2, G12, and v12 were assessed using the tensile test and the relevant ASTM standards. To evaluate substantial variations in the mechanical characteristics of the glassy epoxy and carbon epoxy composites, experimental and numerical modeling will be used. The findings of this study suggest that silica nanoparticles improve the mechanical properties of composite materials. As a result, performance and strength are enhanced when using these reinforced epoxy compounds in structural applications.